2016
DOI: 10.1002/clc.22585
|View full text |Cite
|
Sign up to set email alerts
|

Antianginal Efficacy of Ivabradine/Metoprolol Combination in Patients With Stable Angina

Abstract: Medical treatment is the main clinical strategy for controlling patients with chronic stable angina and improving their quality of life (QoL). Ivabradine treatment on top of metoprolol decreases angina symptoms and improves QoL in patients with stable angina and coronary artery disease (CAD). This is a post hoc analysis (636 CAD patients given ivabradine/metoprolol free combination) of a prospective, noninterventional study that included 2403 patients with CAD and stable angina. Data were recorded at baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…In a different study, 58 59 ivabradine added to metoprolol was shown to improve angina symptoms and QOL in 636 patients with stable angina. Angina attacks were reduced from 2.0/week to 0.2/week (P<0.001) and sublingual nitroglycerin use reduced from 1.4 times/week to 0.1 times/week (P<0.001).…”
Section: Fixed-dose Combined Therapy: New Perspectivesmentioning
confidence: 98%
“…In a different study, 58 59 ivabradine added to metoprolol was shown to improve angina symptoms and QOL in 636 patients with stable angina. Angina attacks were reduced from 2.0/week to 0.2/week (P<0.001) and sublingual nitroglycerin use reduced from 1.4 times/week to 0.1 times/week (P<0.001).…”
Section: Fixed-dose Combined Therapy: New Perspectivesmentioning
confidence: 98%
“…The clinical characteristics, cardiovascular (CV) risk factors, treatment, and outcomes of patients with CAD have changed markedly over the years. Most of the existing data regarding the epidemiology of CAD are relatively old, often focus on 1 manifestation of disease (eg, stable angina) or pertain to acute coronary syndromes, and are often restricted to a single country or a specific geographic region, particularly North America or Western Europe . Thus, there is a need for robust contemporary data in stable CAD representing >1 region and addressing more than symptomatic angina.…”
Section: Introductionmentioning
confidence: 99%
“…Data were recorded at baseline and at 1 month and 4 months after inclusion. Adherence was not a major concern in this study despite free combination 30 …”
Section: Role Of Ivabradine In Different Cardiovascular Diseasesmentioning
confidence: 71%